Non-invasive assessment of adrenocortical function in captive Nile crocodiles (Crocodylus niloticus) and its relation to housing conditions - Myburgh, Jan G. (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2012.